The Influence of Life Skills Education, Islamic Work Ethic and Creative Economy on the Welfare of Muslim Home Industry Business Actors in Medan City - Maulana Muhammad Hamzah; Nurbaiti; Rahmi Syahriza (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of life skills education, Islamic work ethic, and the creative economy on the welfare of Muslim home industry entrepreneurs in Medan City. The problem raised is how these three factors affect the welfare of entrepreneurs in facing business challenges. The method used is a quantitative method with data collection through questionnaires distributed to 100 respondents. Data were analyzed using multiple linear regression to test the influence of each variable. The results show that life skills education, Islamic work ethic, and the creative economy have a significant positive effect on the welfare of entrepreneurs. Life skills education helps entrepreneurs in managing their businesses better, Islamic work ethic builds the values ​​of honesty and responsibility in business, while the creative economy increases competitiveness through innovation. The combination of life skills education, Islamic work ethic, and the creative economy is very important to improve the welfare of Muslim home industry entrepreneurs. These three factors, when implemented in an integrated manner, can create a stronger and more sustainable business ecosystem.